MODEL HARMONISASI HUKUM PENATAAN RUANG KAWASAN PESISIR DALAM PEMBANGUNAN BERKELANJUTAN - Amiruddin Ahmad Dajaan Imami (Indonesian Journal of Dialectics, 2012)
This dissertation, discuss the issues : How the harmonization of the legal constraints in the process of establishment of regulations; and How the harmonization of the legal constraints in implementation regulations in spatial scope in the coastal areas and How the harmonization model in the spatial law in coastal areas to ensure the realization of sustainable development ?Through a descriptive approach: in terms of assessment though interdisciplinary and multidisciplinary, and management approach across sectors, across regions and across stakeholders (integrated), then analyzed it through normative juridical. The conclusions is : 1) The harmonization of legal constraints in the process of establishment regulation of spatial in the coastal areas is  the Ministry of Justice and Human Rights just authorized to coordinate the process of harmonization 2) The harmonization of legal constraints in the implementation regulation of the coastal areas consist of the weakness of substance quality from Law of National Long term Development Plan and its derivatives, and also no sanction can be downed for everyone who against the plans. 3) The harmonization of legal model in environmental and spatial legal system based of theological, ecological and juridical element.